2018
DOI: 10.1620/tjem.244.297
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics of Coaches that Verbally or Physically Abuse Young Athletes

Abstract: Verbal or physical abuse from coaches has a negative impact on young athletes. To prevent abuse against young athletes, it is important to know the characteristics of abusive coaches. This study aimed to elucidate the characteristics of coaches who commit verbal or physical abuse in youth sports teams. A cross-sectional study was conducted with coaches of youth sport teams in Miyagi prefecture, Japan (n = 1,283), using a self-reported questionnaire (response rate was 24.0%). Multivariate logistic regression mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…These results were similar to those of a former report that showed that coaches who had experienced these forms of abuse by their former coaches subsequently tended to use such abuse. They also considered such abuse to be a way to improve the abilities of young athletes (Yabe et al 2018). Parents who had experienced abuse might adapt to it, lessen the negative connotations surrounding it, and approve of its usage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results were similar to those of a former report that showed that coaches who had experienced these forms of abuse by their former coaches subsequently tended to use such abuse. They also considered such abuse to be a way to improve the abilities of young athletes (Yabe et al 2018). Parents who had experienced abuse might adapt to it, lessen the negative connotations surrounding it, and approve of its usage.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have reported on the existence of verbal or physical abuse against athletes from coaches (Kerr and Stirling 2012;Stafford et al 2013Stafford et al , 2015Swigonski et al 2014;Vertommen et al 2017;Yabe et al 2018Yabe et al , 2019Hagiwara et al 2019). One previous study showed that 14.8% of young athletes had experienced verbal abuse and 6.4% had been physically abused by coaches in the preceding year .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the questionnaire directly in young athletes; the incidence of verbal and physical abuse from coaches in the past year was 14.8% and 6.4%, respectively. Verbal abuse has been considered a coaching tool (Swigonski et al 2014) and used with dissatisfaction of the attitude of young athletes (Yabe et al 2018). Although the rate of physical abuse was lower than that of verbal abuse, young athletes reported having experienced physical abuse perpetrated by coaches in this study.…”
Section: Discussionmentioning
confidence: 60%
“…Verbal and physical abuse are supposed to be used to punish inadequate performance or training behavior for improved performance and winning (Stirling and Kerr 2008), which is considered typical of a performance-based environment. Coaches consider that verbal or physical abuse is necessary to improve the ability of young athletes (Yabe et al 2018). However, coaches tend to be unaware of the negative impacts of their behaviors on young athletes (Carlsson and Lundqvist 2016).…”
Section: Discussionmentioning
confidence: 99%